1979
DOI: 10.1038/bjc.1979.99
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mutagenesis and malignant transformation by dihydrodiols from benz[a]anthracene and 7,12-dimethylbenz[a]anthracene

Abstract: Summary.-Five dihydrodiols derived from benz [a]anthracene (BA) and 4 dihydrodiols derived from 7,12-dimethylbenz [a]anthracene (DMBA) have been tested, together with the parent hydrocarbons, for their abilities to induce mutations to 8-azaguanine resistance in V79 Chinese hamster cells and malignant transformation in M2 mouse fibroblasts. The syn-and anti-isomers of benzLa]anthracene 8,9-diol 10,11-oxide were also tested for biological activity in these two systems. The non-Kregion 1,2-and 3,4-dihydrodiols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 37 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Earlier reports from our laboratory have shown that significant uptake of BP in the cytoplasm of human neonatal foreskin (HNF) cells in culture is observed at 12 hours; Cunder these conditions, BP has been shown to bind to a cytoplasmic protein complex (12). Subsequently, optimum accumulation in the nucleus is observed at 24 hours.…”
Section: Ifmentioning
confidence: 86%
See 4 more Smart Citations
“…Earlier reports from our laboratory have shown that significant uptake of BP in the cytoplasm of human neonatal foreskin (HNF) cells in culture is observed at 12 hours; Cunder these conditions, BP has been shown to bind to a cytoplasmic protein complex (12). Subsequently, optimum accumulation in the nucleus is observed at 24 hours.…”
Section: Ifmentioning
confidence: 86%
“…A major portion of the PNH (90%) was found bound to the cytoplasmic protein complex and eventually transported to the nucleus as unmetabolized BP (12). In addition, we found EG-3 H]BP bound to an acid extractable, non-histone, nuclear protein in the low passage cells, 24 hours after carcinogen treatment (J. Oldham, R. Tejwani and G.E.…”
mentioning
confidence: 81%
See 3 more Smart Citations